Epitheloid hemangioendothelioma of the urinary bladder: A case report of a rare entity - Deb, Pratap Kumar; Roy, Rakesh; Roy, Shravasti; Roy, Sayak (Indian Journal of Case Reports, 2024)
Epithelioid hemangioendothelioma (EHE) is a rare, often multifocal, intermediate-grade vascular sarcoma arising from the endothelial cells. Their behavior is intermediate between hemangioma and conventional angiosarcoma. Their rarity and unpredictable clinical behavior result in our still limited understanding and treatment options for this variety of tumors. Molecular diagnostic tools like the presence of WWTR1-CAMTA1 fusion have been developed to aid this challenging diagnosis. There is no definitive consensus on the management of patients with this disease and no commonly accepted treatment strategies have been found to be effective, particularly in the metastatic setting. When possible, surgery with clear margins should be considered in case of localized disease. Here, we not only present such a rare case of EHE of the urinary bladder but also provide a comprehensive discussion on the present treatment modalities offered, as found through a thorough search of the published studies. Finally, more studies are required to establish a standard of care for this rare entity.